Improving 7 Grade Students’ Speaking Skill by Using Vlog Activity - Halliza, Mutiya Halliza; Putri, Reliska Yulita; Putro, Nur Hidayanto Pancoro Setyo (EDUPEDIA Publisher, 2024)
This research was classroom action research and applied one cycle. The aim of this research was to find out the students’ improvement of using vlog in speaking skill. This classroom action research was implemented at 7 grade students of SMP BOPKRI 3 Yogyakarta. The population was ninety one students which consisted of four classes. In this research, the researchers took one class as a sample there were 23 students in A class. In collecting the data the researchers used pre-test, post-test and questionnaires. After implemented the vlog, the researchers analyzed the results of students speaking skill such as: students’ motivation, vocabulary, and pronunciation were improving. It can be seen from the comparison of pre and post questionnaires to know students’ condition before and after the researchers gave the treatment. Next, based on the pre-test and post-test, the researchers found the students’ score was increasing. The pre-test result was 48, 1 and the post-test result was 75,91. Therefore, it can be concluded that students prefer to study English particularly speaking skill by using vlog as a media, which it was the effective strategy in teaching English.